Genesis of legal regulation of relations according to the contract of carriage in codification acts of civil law on the territory of Ukraine - Лукасевич-Крутник, Ірина Степанівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article investigates the development of legal regulation of relations according to the contract of carriage in codification acts of civil law on the territory of Ukraine. It analyzes the provisions of codified acts, the historical periods of legal regulation of relations under the contract of carriage are distinguished in particular the period of formation, development, transformation and up-to-date period. The period of formation in legal regulation of relations under the contract of carriage ( the XIth century – the end of the XIIIth century) is characterized by the absence of legal regulation of contractual relations of transportation in the codification acts of civil law on the Ukrainian territories. The period of the development in the legal regulation of relations under the contract of carriage (the end of the XIIIth century – the beginning of XXth century.) during which some codification acts of civil law on the Ukrainian territory state that the relations of carriage are the subject to legal regulation, but the agreement of carriage is not considered as an individual form of civil and legal obligations. The period of transformation in the legal regulation of relations under the contract of carriage (the beginning of the XXth century - the end of the XXth century) is characterized by numerous changes in the legal regulation of relations under the contract of carriage. In the Civil Code of the Russian Empire in 1905 the first contract of carriage traffic is allocated as an independent form of commitment. The contract of carriage is not mentioned in the Civil Code of the Ukrainian SSR in 1922. With the adoption of the Civil Code of the Ukrainian Soviet Socialist Republic in 1963 the contract of carriage is recognized as a separate civil contract. The modern period of legal regulation of relations under the contract of carriage (1991 - 2016) is characterized by the transition to private law principles regulating relations in the field of transportation which is reflected in the rules of the Civil Code of Ukraine, transport codes and statutes.